Semantic-cognitive representation of corruption in the epideictic discourse of Fernando Olivera - Saavedra Arroyo, Valeria Nicole (2022)
This research proposes the description and analysis of the Peruvian political discourse through the cognitive semantics approach. It is based on a selection of expressions, related to the concept of corruption, used in the discourse of the well-known Peruvian politician Luis Fernando Olivera Vega. Methodologically, the expressions were extracted from the first and second segments of the presidential debate held in April 2016; from the "VI International Anti-Corruption Conference" organized by the Contraloría General de la República and from the press conference held around the presentation of the controversial audios of the convicted former presidential advisor Vladimiro Montesinos Torres regarding the presidential elections in June 2021. The article concludes that Olivera is yet another case of an emerging discourse of protest against corruption in Peru, where Olivera embodies the idea that the elected president should be the leading example of virtue.